2017
DOI: 10.25125/engineering-journal-ijoer-aug-2017-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Layered GaSe Crystals Intercalated with RbNO3 Ferroelectric Salt and their Application for Electric Capacitors

Abstract: Abstract-XRD, SEM, EDX investigations as well as wide temperature (T = 5-300 K)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…37 After irradiation with electron fluences of 10 15 and 10 16 cm −2 , a significant decrease in droplets was not detected. In previous work 38 it was shown that Bridgman-grown bulk In 2 Se 3 crystals may contain nanoformations of various compounds of In and Se atoms.…”
Section: Resultsmentioning
confidence: 99%
“…37 After irradiation with electron fluences of 10 15 and 10 16 cm −2 , a significant decrease in droplets was not detected. In previous work 38 it was shown that Bridgman-grown bulk In 2 Se 3 crystals may contain nanoformations of various compounds of In and Se atoms.…”
Section: Resultsmentioning
confidence: 99%